Pelaksanaan Sosialisasi Pencegahan Kebakaran Di Kecamatan Setiabudi Jakarta Selatan - ANDIKA BAGASKARA; Aryo Santiko (Jurnal Ilmu Administrasi Publik, 2022)
This study was conducted to determine the effectiveness of the campaign carried out by the Fire and Rescue Service of Setiabudi District in DKI Jakarta Province. This is descriptive qualitative research with interview and observation methods. Data were obtained from 6 informants, 3 key informants and 3 members of the community. Based on the results of the research, it is known that the fire prevention and control program campaign at the Fire and Rescue Service of South Jakarta is carried out routinely. This campaign activity is carried out directly and indirectly. The obstacles faced are related to the schedule of the campaign activities that often clashes with the public's occupational activities.